15N Fertilizer recovery in different tillage–straw systems on a Vertisol in north‐west Mexico. (21st May 2019) - Grahmann, Kathrin; Dittert, Klaus; Verhulst, Nele; Govaerts, Bram; Buerkert, Andreas
Abstract: Tillage and residue retention affect nitrogen (N) dynamics and nutrient losses and therefore nitrogen use efficiency (NUE) and crop fertilizer use, however, there is little information about residual fertilizer effects on the subsequent crop. Micro‐plots with 15 N‐labelled urea were established in 2014/2015 on a long‐term experiment on a Vertisol in north‐west Mexico. N fertilizer recovery (NFR) and the effects of residual fertilizer N for summer maize ( Zea mays L.) and the subsequent wheat ( Triticum durum L.) crop were studied in three tillage–straw management practices (CTB: conventionally tilled beds; PB‐straw: permanent raised beds with residue retention; PB‐burn: permanent raised beds with residue burning). Fertilizer 15 N recovery rates for maize grain across all treatments were low with an average of 11%, but after wheat harvest total recovered 15 N ( 15 N in maize and wheat straw and grain, residual soil 15 N) was over 50% for the PB‐burn treatment. NFR was lowest in CTB after two cropping cycles (32%). Unaccounted N from applied fertilizer for the maize crop averaged 120 kg 15 N ha −1 after wheat harvest. However, more than 20% of labelled 15 N was found in the 0–90 cm soil profile in both PB treatments after wheat harvest, which highlights the need for long‐term studies and continuous monitoring of the soil nutrient status to avoid over‐application of mineral N fertilizer.